The Needs Of Parents' Of Children With Autism Spectrum Disorder and Relationship With Some Variables - Field study in Lattakia city - Zaitoun , Ahmad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to know the needs of parents’ of children with autism spectrum disorder Lattakia city, also aimed to examine the differences in needs of parents of children with autism spectrum disorder to the variables (sex, age and degree of disability). the research used descriptive analytical method, the sample included (182) parents in the academic year 2016/2017. the research used needs of parents’ of children questionnaire consisted of (40) items, distributed to four areas. the following statistical methods were used: means, t – test, Cronbach Alpha, And One Way ANOVA. Validity of the questionnaire was established though a jury of (7) of the teaching staff at Damascus and Tishreen Universities. Pilot sample consisted of (22) Parents. Reliability was established by Cronbach – Alpha Reliability at lest (0.828). The final results showed that the degree of the needs of parents of children with autism spectrum disorder were higher rated for the sample research. in fact, there were significant differences about the needs of parents of children with autism spectrum disorder related to the sex, but there no were significant differences related to the (age and degree of disability). The research had some suggestions about increase the specially centers which to take care of the children with autism spectrum disorder in Lattakia city.